Gold Nanoparticles Combined Human β-Defensin 3 Gene-Modified Human Periodontal Ligament Cells Alleviate Periodontal Destruction via the p38 MAPK Pathway - Li, Lingjun; Zhang, Yangheng; Wang, Min; Zhou, Jing; Zhang, Qian; Yang, Wenrong; Li, Yanfen; Yan, Fuhua (Frontiers in Bioengineering and Biotechnology, 2021)
Periodontitis is a chronic inflammatory disease with plaques as the initiating factor, which will induce the destruction of periodontal tissues. Numerous studies focused on how to obtain periodontal tissue regeneration in inflammatory environments. Previous studies have reported adenovirus-mediated human β-defensin 3 (hBD3) gene transfer could potentially enhance the osteogenic differentiation of human periodontal ligament cells (hPDLCs) and bone repair in periodontitis. Gold nanoparticles (AuNPs), the ideal inorganic nanomaterials in biomedicine applications, were proved to have synergetic effects with gene transfection. To further observe the potential promoting effects, AuNPs were added to the transfected cells. The results showed the positive effects of osteogenic differentiation while applying AuNPs into hPDLCs transfected by adenovirus encoding hBD3 gene. In vivo, after rat periodontal ligament cell (rPDLC) transplantation into SD rats with periodontitis, AuNPs combined hBD3 gene modification could also promote periodontal regeneration. The p38 mitogen-activated protein kinase (MAPK) pathway was demonstrated to potentially regulate both the in vitro and in vivo processes. In conclusion, AuNPs can promote the osteogenic differentiation of hBD3 gene-modified hPDLCs and periodontal regeneration via the p38 MAPK pathway.